2010
DOI: 10.1001/archinternmed.2010.363
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Breast Cancer Among Postmenopausal Women

Abstract: Background Physical activity has many health benefits. Although greater activity has been related to lower postmenopausal breast cancer risk, important details remain unclear, including type, intensity, and timing of activity, and whether the association varies by subgroups. Methods Within the prospective Nurses’ Health Study, we assessed the associations of specific and total activity, queried every 2–4 years since 1986, with breast cancer risk. Cox proportional hazards models were used to calculate hazard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 32 publications
6
120
0
3
Order By: Relevance
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…HRs for hormone receptor-defined invasive breast cancer according to level of recreational physical activity within the previous 4 years Contrary to most studies, which have not found that the relation between physical activity and breast cancer risk was modified by weight changes before inclusion (9,11,13,21,30), three articles report that the risk decrease associated with baseline physical activity is restricted to postmenopausal women with limited weight gain between youth and baseline (22,31,32). However, a weight gain before baseline may be associated with a decrease in physical activity after baseline (33).…”
Section: Discussionmentioning
confidence: 82%
“…However, the leanness of E3N women did not allow to explore the effect in higher categories of BMI or waist circumference. Similarly, most studies did not observe modifications in this relation according to hormone receptor status during postmenopause (6,10,13,(22)(23)(24)(25)(26). The risk reduction was limited to ER À (27) and PR þ (28) subtypes in two prospective studies and apparent only for postmenopausal ER þ /PR À (29) and ER þ /PR þ (25) cancers in two other studies (no tests for homogeneity).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A comparison of PA measurements in adults revealed that a dose response was seen in the reduction in the risk of developing cancer at higher levels of PA (600-3,999 METs minutes/week and 4,000-7,999 METs minutes/week vs. < 600 METs minutes/week), with risk reduction ranging from 3% to 14% for breast cancer and 10% to 21% for colorectal cancer [19]. Increased PA has also been described as beneficial for post-menopausal women diagnosed with breast cancer, and the timing of initiating exercise is also important [20]. The risk of gastric cancer was found to be 21% lower in persons with high levels of PA than in those with low levels of PA [21].…”
Section: Effects Of Physical Activity On Cancer Preventionmentioning
confidence: 99%